Perancangan Antarmuka Pengguna Aplikasi Pengingat Jadwal Vaksinasi Hewan Peliharaan menggunakan Human-Centred Design (HCD) - Naila Elma Nuarisya; Ismiarta Aknuranda; Alfi Nur Rusydi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Pets especially dogs and cats need to get vaccines to prevent the occurrence of illness and mortality in pets caused by a virus or bacterial infections and to prevent transmission of disease to humans. However, sometimes the animal owner pays little attention and sometimes forgets the vaccination schedule for his beloved animal. The purpose of this study is to design a user interface for a mobile-based application to remind a pet vaccination schedule. The application is designed to meet user needs, is easy to use, and provides a good experience for users. The approach used for designing the application is Human-Centered Design (HCD). The design of the user interface is in the form of a high-fidelity prototype based on software, and then it is evaluated by usability testing techniques. There are 2 alternative designs produced to be tested to users of animal owners and veterinarians. The evaluation results of the two design alternatives get a score above the average SEQ score, thus showing that the user interface design is easy to use. But the design still needs some improvement in the user interface. Based on the conclusions of the evaluation results of the two users, design A received an average score of 6.23 while design B received an average score of 6.27. Then the design chosen and most sought after by users is design B.